Laparoscopic Proximal Gastrectomy Versus Laparoscopic Total Gastrectomy for Proximal Gastric Cancer: A Systematic Review and Meta−Analysis - Tian, Peirong; Liu, Yang; Bian, Shibo; Li, Mengyi; Zhang, Meng; Liu, Jia; Jin, Lan; Zhang, Peng; Zhang, Zhongtao (Frontiers in Oncology, 2021)
Background: To compare laparoscopic proximal gastrectomy (LPG) and laparoscopic total gastrectomy (LTG) with regard to outcomes, including efficacy and safety, in patients with proximal gastric cancer. Methods: Original English-language articles comparing LPG and LTG for proximal gastric cancer up to November 2019 were systematically searched in the Embase, PubMed, Cochrane Library, Web of Knowledge and ClinicalTrials.gov databases by two independent reviewers. Our main endpoints were surgery-related features (operation time, blood loss, harvested lymph nodes, and postoperative hospital stay), postoperative complications (anastomotic leakage, anastomotic bleeding, anastomotic stenosis, and reflux esophagitis) and oncologic outcomes (5-year overall survival and recurrent cancer). Results: Fourteen studies including a total of 1282 cases (510 LPG and 772 LTG) were enrolled. Fewer lymph nodes were harvested (WMD = -13.33, 95% CI: -15.66 to -11.00, P < 0.00001) and more postoperative anastomotic stenosis (OR = 2.03, 95% CI: 1.21 to 3.39, P = 0.007) observed in LPG than LTG. There were no significant differences in other explored parameters between the two methods. However, based on a subgroup analysis of digestive tract reconstruction, LPG with esophagogastrostomy (LPG-EG) had shorter operative time (WMD = -42.51, 95% CI: -58.99 to -26.03, P < 0.00001), less intraoperative blood loss (WMD = -79.52, 95% CI: -116.63 to -42.41, P < 0.0001), and more reflux esophagitis (OR = 3.92, 95% CI: 1.56 to 9.83, P = 0.004) than was observed for LTG. There was no difference between LPG performed with the double tract anastomosis/double-flap technique (DT/DFT) and LTG. Conclusion: LPG can be performed as an alternative to LTG for proximal gastric cancer, especially LPG-DT/DFT, with comparable safety and efﬁcacy.